A Study on Situational Awareness Security and Privacy of Wearable Health Monitoring Devices. (2016) - Bellekens, Xavier; Nieradzinska, Kamila; Bellekens, Alexandra; Seeam, Preetila; Hamilton, Andrew; Seeam, Amar
No abstract available